(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Volosenko A. V. Diagnosing the level of students’ readiness in the economic university to creativeself-realization in their future professional activity. The level of students — future lecturers’ readiness to creative self-realization is analyzed. Students’ ideas concerning means and ways of enhancing the effectiveness of their self-realization in the educational process are summarized.